The Health Services (London : C. W. Publishing Ltd.)
1944-05 1944 1940s 23 pages 16 Illness in industry. Dr. D.C. Norris, an authority on industrial medicine, calculated that the total number of industrial accidents causing injury in Great Britain during the pre-war years was about 13 millions annually. Yet in 1939 there were only 320 factory inspectors to inspect 283,000 premises; only 8 medical inspectors ; and the total number of doctors employed full-time in industry was about 30. (The number employed both full-time and part-time has now risen to 850.) Some trades are more dangerous to health than others.[superscript 5] Industrial diseases in factories (1935)............. 66 per 100,000. Industrial diseases in mines (1935) ...............1,980 per 100,000 Accidents in factories (1936)................13 fatal: 3,420 non-fatal. Accidents in mines...........................114 fatal ; 21,130 non-fatal. Yet in 1939 there was only one medical inspector of mines. Unattended Disease. At the Peckham Health Centre, where over a thousand families (almost 4,000 individuals) were subjected to preventive medical overhaul, it was found that only 14 per cent. of the men and 4 per cent. of the women were without disorder. Only a very small percentage of those suffering from some disorder were aware of it, and of these again only a very small percentage were under medical treatment.[superscript 6] £.s.d. of the Health Services. The Cost of Ill-Health, 1936.[superscript 6] Work lost annu lly [annually] through sickness estimated at £120,000,000 Treatment and maintenance of sick persons... £183,000,000 £303,000,000 The Cost of Measures to prevent Ill-Health, 1936. Prevention of ill-health (school medical service, maternity and child welfare, etc.) .......... £13,000,000 Environmental services which contribute to health (housing, water, sewerage, etc.) ....... £100,000,000 £113,000,000 NOTES — The figures are drawn from the following sources :— 1. H.M. Vernon. Preventive for Improving British Association for Labour Legislation. 2. Infant Mortality in Scotland. H.M.S.O., 1943. 3. Birth, Poverty, and Wealth. R.M. Titmuss, pp. 26, 96. 4. The State of Public Health, 1938. H.M.S.O. 5. P.E.P. Report on the British Health Services, 1937. 6. The Peckham Experiment. 15X/2/98/10